2018
DOI: 10.1371/journal.pone.0189452
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive meta-analysis of circulation miRNAs in glioma as potential diagnostic biomarker

Abstract: Glioma is the most common malignant intracranial tumour. Recently, several publications have suggested that miRNAs can be used as potential diagnostic biomarkers of glioma. Here we performed a meta-analysis to identify the diagnostic accuracy of differentially expressed circulating miRNAs in gliomas. Using PubMed, Medline and Cochrane databases, we searched for studies which evaluated a single or panel of miRNAs from circulating blood as potential biomarkers of glioma. Sixteen publications involving 23 studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 46 publications
1
33
0
Order By: Relevance
“…However, the major shortcoming of using blood-based miRNA for CRC screening is the detection specificity. This is because miRNAs might arise from other cancer(s) [64,65], depression [66], and virus infection(s) [67,68]. Therefore, faecal-based miRNA detection may be an alternative option [57,59,60,69].…”
Section: Screening Tools Under Developmentmentioning
confidence: 99%
“…However, the major shortcoming of using blood-based miRNA for CRC screening is the detection specificity. This is because miRNAs might arise from other cancer(s) [64,65], depression [66], and virus infection(s) [67,68]. Therefore, faecal-based miRNA detection may be an alternative option [57,59,60,69].…”
Section: Screening Tools Under Developmentmentioning
confidence: 99%
“…There have been multiple studies examining 'free-circulating' miRNAs in glioma patients with varying success. A recent meta-analysis of these studies found the specificity and sensitivity of circulating miRNAs was 0.87 and 0.86, respectively, while noting the large heterogeneity of circulating miRNAs within the included studies [17]. The heterogeneity is likely due to differences in data normalization used in qRT-PCR studies, with no universally accepted endogenous housekeeping control [17].…”
Section: Mirnas Dysregulated In Idh-mutant Grade Ii-iii Gliomas Provimentioning
confidence: 99%
“…A recent meta-analysis of these studies found the specificity and sensitivity of circulating miRNAs was 0.87 and 0.86, respectively, while noting the large heterogeneity of circulating miRNAs within the included studies [17]. The heterogeneity is likely due to differences in data normalization used in qRT-PCR studies, with no universally accepted endogenous housekeeping control [17]. Interestingly, the majority of miRNAs identified in our exosomal signature have not been previously identified in 'free-circulating' studies.…”
Section: Mirnas Dysregulated In Idh-mutant Grade Ii-iii Gliomas Provimentioning
confidence: 99%
“…These characteristics of miRNAs make them potentially useful diagnostic, prognostic, and predictive biomarkers for cancer research (12). A few biomarkers studies have demonstrated early diagnosis and progression could be predicted by tissue or blood miRNAs expression (13).…”
Section: Introductionmentioning
confidence: 99%